Not Minding the Gap: Intercultural Shakespeare in Britain - Panjwani, Varsha (Multicultural Shakespeare: Translation, Appropriation and Performance, 2017)
The article takes issue with the perceived space/gap between the multiple identities of mixed-heritage groups, as most of these people often pick and choose elements from all of their identities and amalgamate them into a cross-cultural whole. In recent years, such mixed-heritage groups in the U.K. have increasingly found cultural expression in Shakespeare. Focusing specifically on a number of recent Shakespearean productions, by what I term Brasian (my preferred term for British-Asians as it suggests a more fused identity) theatre companies, the article demonstrates how these productions employ hybrid aesthetic styles, stories, and theatre forms to present a layered Braisian identity. It argues that these productions not only provide a nuanced understanding of the intercultural map of Britain but are also a rich breeding ground for innovative Shakespeare productions in the U.K.